Alfalfa (Medicago sativa L.) growth and yield in desert soil fertilized with raw and anaerobically digested cattle manure. (10th February 2022) - Abubaker, Jamal; Alaswd, Abdalla; Mohammed, Nouriya Salah; Zeadani, Hassan El‑; Khalifa, Massoudah
Abstract: Anaerobic digestion is a biological method used to treat organic wastes for bioenergy production and it creates nutrients rich digestate that is used as a soil fertilizer. However, the ability of digestate to improve the productivity of desert soil is not well documented. A pot experiment was conducted to test the efficiency of raw (RM) and anaerobically digested cattle manure (DM) in supporting alfalfa ( Medicago sativa L.) seeds germination, growth and yield in virgin desert soil. Treatments of combination with urea and biofertilizer (local rhizobium strain) (BF) were also used beside the untreated soil as a control, and the application rate of fertilizers was corresponded to 150 kg Tot N ha −1 . During the experiment, final germination percentage (FGP %), germination index (GI), a total number of plant stems (TS), plant height, deficiency symptoms, number of nodules (NN), dry biomass of shoot, root, and total biomass were all assessed. The results showed that the application of DM and RM increased all parameters as compared with the control treatment. In comparison with other treatments, DM gave the highest germination, lower deficiency symptoms, taller plants, increased TS, increased NN and biomass yield (i.e., root, shoot and total biomass). Furthermore, combination with urea reduced all measured parameters in comparison with RM and DM sole treatments. It was concluded that the best management for improving alfalfa growth and yield at the cultivation in virgin desert soil is to apply anaerobically digested cattle manure as a soil fertilizer.